EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN PEMAHAMAN KONSEP IPA - Ansori (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aimed to analyze the effectiveness of Augmented Reality (AR)-based learning media in improving science concept understanding among fifth-grade students at MI At-Taqwa Bondowoso. The research was conducted from August to September 2025 using a quasi-experimental design with a pretest-posttest control group format. The participants consisted of two classes: an experimental group that received AR-based learning and a control group that was taught using conventional instructional methods. The research instrument was a science concept understanding test that had been validated and tested for reliability. Data were analyzed using a paired sample t-test to measure improvements within each group, an independent samples t-test to examine differences between the two groups, and N-Gain analysis to determine the magnitude of conceptual improvement. The results indicated that the mean score of the experimental group increased from 58.40 to 84.20, while the control group improved from 57.80 to 71.60. The paired sample t-test showed significant improvements in both groups (Sig. 0.000 < 0.05), with a higher t-value in the experimental group (t = 14.562). The independent samples t-test revealed a significant difference between the two groups (t = 6.482; Sig. 0.000 < 0.05). The N-Gain score for the experimental group was 0.72 (high category), whereas the control group achieved 0.33 (moderate category). Therefore, AR-based learning media proved to be effective in enhancing science concept understanding among Madrasah Ibtidaiyah students.